PENERAPAN UANG PENGGANTI DALAM PERKARA TINDAK PIDANA KORUPSI (STUDI KASUS : PUTUSAN NOMOR 1046 K/PID.SUS/2017) (Lex Jurnalica, 2019)
AbstrakCorruption crimes in Indonesia have been very widespread and have come into the whole layer of community life. Its development continues to increase from year to year, in the number of cases and the amount of state financial losses as well as in terms of the quality of corruption that is carried out increasingly systematic that has entered all aspects of community life. Corruption acts are a violation of the social rights and economic rights of the community, so that the criminal acts of corruption are no longer classified as ordinary crimes but have become extraordinary crimes. So in an effort eradicationcan no longer be done on a regular basis, but it is demanded extraordinary ways.From the background above, it is the problem in the writing of this law that is how the arrangement of the types of punishment in the Corruption Act of law, as well as how the process of applying a substitute for money in criminal matters Case studies corruption verdict No. 1046 K/PID. SUS/2017. Considering this study uses a normative approach, the collection of legal materials is done by identifying and inventing procedures of primary legal materials and secondary legal substances and tertiary legal materials.The results showed that the main goal weighed the types of sanctions in the Criminal Acts of Corruption Lawis to provide a deterrent effect against the victims who have detrimental to the state in order to restore and restore the state's finances by paying Additional criminal in the form of substitute money and the replacement of the money in this case is very unwarranted, because the defendant is not proven to accept